Legend of the seeker. Complete first season. ([United States] : Abc Studios, 2009)
After his father is murdered, a son's search for justice begins a momentous fight against tyranny. Includes all 22 episodes, plus exclusive bonus features.
TV rating: TV-14.
DVD, widescreen; 5.1 Dolby digital.
English audio.
Keywords: Fantasy -- Drama; Wizards -- Drama; Television series; Fiction television programs; Television programs for the hearing impaired